Industrial relations : theory and practice - Colling, Trevor; Terry, Michael (John Wiley & Sons, 2010)
This revised edition of Industrial Relations: Theory and Practice follows the approach established successfully in preceding volumes edited by Paul Edwards. The focus is on Britain after a decade of public policy which has once again altered the terrain on which employment relations develop